Vitamin D: Mechanisms and Challenges of a Pandemic (Research, Society and Development, 2025)
Vitamin D is an essential pro-hormone that plays a critical role in human health, aiding the immune response through the absorption of essential minerals such as calcium, phosphate and magnesium. It also contributes to the inhibition of TH1 and stimulation of T cells, key components in the body's defense. The objective is to explain mechanisms, in addition to listing the impact that this vitamin has not only on the development of the human body, but also against various diseases, avoiding a pandemic of vitamin D deficiency and its consequences. This study reviewed articles published between 2010 and 2023, selecting those which provided the most significant contributions. Evidence indicates that adequate vitamin D supplementation can reduce the risk of type 2 diabetes by up to 76% and the risk of developing certain types of cancer by 66%, as well as being beneficial in cases of severe covid-19 and other diseases. Obese people often have lower levels of vitamin D, complicated by polymorphisms in receptors that can affect the absorption of the vitamin. This study aims to highlight the effectiveness of vitamin D in disease prevention and warns of the global deficiency of this vitamin. We conclude that awareness strategies and targeted interventions are essential, especially for those in at-risk groups, to reduce the persistent pandemic of vitamin D deficiency worldwide.